Impact of the ASEAN economic community on ASEAN production networks - Kornkarun Cheewatrakoolpong; Chayodom Sabhasri; Nath Bunditwattanawong (Asian Development Bank Institute (ADBI), 2013)
Empirical evidence suggests that the emergence of international production networks in East Asia results from market-driven forces such as vertical specialization and higher production costs in the home countries and institutional-led reasons such as free trade agreements. The growth in trade in parts and components since the 1990s, especially with the People's Republic of China (PRC), one of the important major assembly bases, confirms the existence of international production sharing in the region. Also, a decline in the share of parts and components trade in several members of the Association of Southeast Asian Nations (ASEAN) such as Indonesia and Thailand indicates the increasing importance of the ASEAN countries as assembly bases for Japanese multinational enterprises (MNEs). This paper examines two industries - autos and auto parts, and hard disk drives (HDDs) - to understand international production networks. The study examines the structure of vertical intra-industry trade among East Asian countries, especially members of the Association of Southeast Asian Nations, depicts international production sharing in the selected industries, namely HDD, and automobiles and automotive parts, in the region. The study also points out the importance of the People's Republic of China and Thailand as assembly bases. It concludes that investment promotion policies contributed more to the emergence of international production networks than free trade agreements.
Keywords: F14; 330; asean; production networks; asean economic community; east asia; vertical specialization; Regionale Wirtschaftsintegration; Internationale Arbeitsteilung; Kraftfahrzeugzulieferer; Kraftfahrzeugindustrie; ASEAN-Staaten